Skin photobiological effect induced by BL: Clinical manifestation, mechanisms, and protection against photodamages - Tao Zhang; Malyn Ungsurungsie; Liu Yue; Junxiang Li; Baoxia Zhuang; Wenyu Ding; Xuhui Li (Journal of Dermatologic Science and Cosmetic Technology)
Over the last decade, the rapid advances of life sciences have significantly increased public awareness and comprehension of dermatological knowledge, resulting in widespread acceptance of scientific skincare in society. The scope of photoprotection has expanded to encompass not only ultraviolet radiation but also visible light (including blue light). Furthermore, photoprotection methods have evolved from light blocking to the repair of cellular damage caused by prolonged light exposure via biological signaling pathways. Blue light (BL) is the portion of sunlight between 400 nm（violet）and 500 nm (cyan), that can penetrate deep into biological tissues, with up to 20 % reaching subcutaneous tissues. Similar to UV damage, BL can cause oxidative stress, persistent pigmentation, and extracellular matrix degradation, resulting in skin symptoms such as hyperpigmentation, dullness, lack of radiance, uneven skin tone, and wrinkles. This study investigates the clinical manifestations of BL-induced skin photodamages, as well as the underlying biological mechanisms and proposes rational photoaging prevention strategies.